EFFICACY OF TRANSSCLERAL LASER CYCLOPHOTOCOAGULATION IN MICROPULSE MODE IN PATIENTS WITH REFRACTORY GLAUCOMA - Boboev S.A; Boboev S.S,; Kadirova A.M; Abdullaeva D.R. (Scholar Express Journals, 2023)
Increasing the effectiveness of glaucoma treatment is one of the most urgent tasks in ophthalmology due to the high medical and social significance of this disease associated with a high prevalence rate and severity of outcomes, often leading to blindness and disability. Despite the successes achieved in medical, laser and surgical treatment of glaucoma, the probability of amblyopia and blindness has remained steadily high for many decades. The importance of intraocular pressure (IOP) compensation to stabilize the glaucoma process, which requires long-term, sometimes lifelong, local hypotensive therapy, has been proven by a number of clinical studies. In this regard, it should be noted that continuous use of local hypotensive drugs often leads to pathological changes of ocular surface tissues of toxic-allergic, xerotic and inflammatorydegenerative nature, which significantly reduces the quality of life of patients. Negative effect of local hypotensive therapy on ocular surface in combination (in some patients) with its inefficiency determines the relevance of laser methods of glaucoma treatment, which main advantages are low injury rate, absence of serious intra- and postoperative complications, and possibility to perform the intervention (including reoperation) on an outpatient basis.
Keywords: glaucoma treatment; direct coagulation effect; intraocular fluid